Chemoreceptors and feeding in calanoid copepods (Arthropoda: Crustacea). - Friedman, M M (1975)
Ultrastructural studies of the mouthparts of the calanoid copepod Diaptomus pallidus have revealed the presence of numerous chemoreceptors, and the apparent absence of mechanoreceptors. The setae contain no muscles, and the setules are noncellular extensions of their chitin wall. This allows a new insight into the selective feeding of zooplankters.